Perceptions Matter: An Expanded Operationalization of Betrayal Trauma Using Perceived Betrayal. - Griffith, Elizabeth L.; Bedford, Lee A.; Boals, Adriel; Sternad, Rose (Journal of Loss & Trauma, 2025)
Betrayal Trauma Theory (BTT) posits that betrayal during trauma increases the likelihood of developing adverse psychological symptoms. Studies based on BTT often objectively dichotomize traumas as high or low betrayal traumas based on objective details of the event; however, betrayal may also be subjective. Recent literature suggests that the subjective details may be important when considering outcomes of trauma exposure. We hypothesize that one's perception of betrayal is an important predictor of trauma-related outcomes, above and beyond variance explained by objective measures of betrayal. We asked a sample of 224 trauma-exposed participants recruited from MTURK to complete measures of both objective betrayal and subjective betrayal associated with their trauma, along with measures of PTSD, depressive, and dissociative symptoms. We successfully replicated previous findings that objective high betrayal was associated with worse trauma-related outcomes. We similarly found that subjective betrayal was also associated with worse trauma-related outcomes. Importantly, using hierarchical regressions, we found that subjective perceptions of betrayal predicted symptoms of PTSD, depression, and dissociation independently, even after accounting for variance explained by objective betrayal. These findings indicate that perceptions of betrayal are an important consideration when attempting to understand how betrayal can affect trauma-related outcomes.